Prognostic value of prehospital quick sequential organ failure assessment score among patients with suspected infection. (October 2019) - Vaittinada Ayar, Prabakar; Delay, Mathieu; Avondo, Aurélie; Duchateau, François-Xavier; Nadiras, Pierre; Lapostolle, Frédéric; Chouihed, Tahar; Freund, Yonathan
Abstract : Objective: After the third international consensus on sepsis released its new definitions, the prognostic value of quick sequential organ failure assessment (qSOFA) score has been confirmed in the emergency department. However, its validity in the prehospital setting remains unknown. The objective of the study was to assess its accuracy for prehospital patients cared by emergency physician-staffed ambulances (services mobiles d'urgence et de réanimation SMUR). Patients and methods: This was a prospective observational multicenter cohort study ( N = 6). All consecutive patients with prehospital clinical suspicion of infection by the emergency physician of the SMUR emergency medical service were included. Components of qSOFA were collected, and the patients were followed until hospital discharge. The primary end point was in-hospital mortality, censored at 28 days. Secondary end points included ICU admission longer than 72 h and a composite of 'death or ICU stay more than 72 h'. Results: We screened 342 patients and included 332 in the analysis. Their mean age was 73 years, 159 (48%) were women, and the most common site of infection was respiratory (73% of cases). qSOFA was at least 2 in 133 (40%) patients. The overall in-hospital mortality was 27%: 41% in patients with qSOFA of at least 2 versus 18% for qSOFA less than 2 (absolute difference 23%; 95% confidence interval: 13–33%, P < 0.001). The overall discrimination for qSOFA was poor, with an area under the receiver operating characteristic curve of 0.69 (95% confidence interval: 0.62–0.74). Conclusion: In this large multicenter study, prehospital qSOFA presents a strong association with mortality in infected patient, though with poor prognostic performances in our severely ill sample. Abstract : Supplemental Digital Content is available in the text.